Concept of Legitimation of Zakat Amil Institutions: Muzakki Perspective - Kanji, Lusiana; Pagalung , Gagaring; Damayanti, Ratna Ayu; Kusumawati, Andi (Journal of Ecohumanism, 2025)
The low trust public towards amil zakat becomes trigger muzakki more choose channel the zakat in a way traditional . Objective research This is browse in a way deep The meaning of zakat for muzakki as something obligations ordered by God​ and how meaning Zakat amil institutions in the eyes society , why more choose channel direct the zakat to mustahiq and no through institution existing official .​ Methodology the author 's research use in study This is with combine two paradigm that is Paradigm Interpretative with approach Phenomenology and Paradigms Religious based on truth revelation Lord . Research results This showing From the corner look muzaki , legitimacy Zakat amil institutions depend on contracts social with the community served . This emphasize transparency , fairness , and sharia compliance in fund management . For strengthen legitimacy , institution need transparent in use of funds, involving muzakki , and run the program accordingly need public . With method this , them can build trust and effectiveness in overcome problem social , economic , and moral.